HEDONIC SHOPPING MOTIVATION: IMPULSE BUYING IN SURABAYA CONSUMER - Fachrudy Asj’ari; I Made Bagus Dwiarta; Sigit Prihanto Utomo; Hartono Hartono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research intended to asses the hedonic shopping motivation to the royal plaza Surabaya consumer impulse buying which must be performed in connection with performance of the employee. This research was conducted at the royal plaza Surabaya which covered consumer as respondent. This research by utilizing Structural Equation Modeling (SEM), the technique was processed with AMOS program 6.0 to analyze some hypothesis. The intercorrelation models between these variables in this study revealed that hypothesis have significant correlation. The result of this research were empirical date of the development of the theoretical of marketing and practice management.